Innovative materials and systems for energy harvesting applications - Mescia, Luciano, 1973-; Losito, Onofrio, 1969-; Prudenzano, Franceso, 1964- (Engineering Science Reference, an imprint of IGI Global, 2015)
"This book reports on some of the best tools and technologies available for powering humanity's growing thirst for electronic devices, including piezoelectric, solar, thermoelectric, and electromagnetic energies"-- Provided by publisher.
"Premier reference source"--Cover.
Keywords: Energy harvesting -- Equipment and supplies.; Transducers.; elektronické knihy; electronic books